2001
DOI: 10.1177/108705710100600205
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Miniaturized 384-Well High Throughput Screen for the Detection of Substrates of Cytochrome P450 2D6 and 3A4 Metabolism

Abstract: The identification of a large number of biologically active chemical entities during high throughput screening (HTS) necessitates the incorporation of new strategies to identify compounds with druglike properties early during the lead prioritization and development process. One of the major steps in lead prioritization is the assessment of drug metabolism mediated by the cytochrome P450 (CYP) enzymes to evaluate the potential drug-drug interactions. CYP2D6 and CYP3A4 comprise the main human CYP enzymes involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…[27][28][29] Alternatively, to minimize the negative effect of DMSO on assay performance, test compounds could be delivered as redissolved dry films, according to recent data demonstrating comparable activity for compounds delivered in DMSO stocks or as dried compound films. 23 The latter approach may be preferable for further development of fully automated miniaturized assays and robotic applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] Alternatively, to minimize the negative effect of DMSO on assay performance, test compounds could be delivered as redissolved dry films, according to recent data demonstrating comparable activity for compounds delivered in DMSO stocks or as dried compound films. 23 The latter approach may be preferable for further development of fully automated miniaturized assays and robotic applications.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] In addition, fluorometric assays in a 384-well format for the CYP3A4 and CYP2D6 isozymes have also been described. 23 However, many undesirable features of the generic (unmodified) fluorescent molecules, such as poor aqueous solubility, high background fluorescence (e.g., the fluorescence of unmetabolized substrate), and low signal-to-background ratios, limit their applications for low-volume ultra-high-throughput formats. Recently, highly miniaturized formats for primary screening assays involving several important pharmaceutical targets were developed.…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes have evolved to act as molecular incinerators in the liver and are known to interact with a wide range of substrates, making CYP assays ideal tools for quality assessment of diverse sets of compounds. In this study, we employed CYP 1A2 and 2D6 isozymes because we have previously confirmed that these assays perform well in 1536-well microplate formats, show low sensitivity to DMSO, 11,12 and are inhibited by a large number of compounds in typical compound collections (see PubChem AIDs 410 and 891, respectively). We examined compound storage in 1536-well microplates because this is central to our screening platform.…”
Section: Introductionmentioning
confidence: 99%
“…the assays reported here should complement the current higher throughput approaches for the evaluation of P450-related drugdrug interactions. [16][17][18]…”
Section: Introductionmentioning
confidence: 99%